Strategies for Strengthening Local Institutions in the Regency of Central Maluku - Ruhunlela, Victor Sanjak; de Fretes, Judy; Rukoyah, Rukoyah (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2025)
This study examines strategies to strengthen local institutions in Piru Village, West Seram Regency, particularly the Negeri and Saniri institutions. These traditional bodies, part of the community governance system in Maluku, face challenges that weaken their roles. Using a qualitative approach, the study identifies key factors influencing institutional decline and explores how members empower themselves through education and training. The findings reveal strong enthusiasm among members to enhance their knowledge and skills, significant support for those who can participate in learning activities, and high expectations that trained individuals will share their knowledge with others. Overall, the study highlights the importance of collective commitment and knowledge-sharing as essential strategies for strengthening the capacity and sustainability of local institutions in West Seram Regency.